Design and fabrication of customized brain slice matrices using CAD and 3D printing technology. - Yosuke Yamazaki; Maki Yuguchi; Bin Honjo; Keitaro Isokawa (PLoS ONE)
This study presents a novel method for creating customized brain slice matrices using Computer-Aided Design (CAD) and 3D printing technology. Brain Slice Matrices are essential jigs for the reproducible preparation of brain tissue sections in neuroscience research. Our approach leverages the advantages of 3D printing, including design flexibility, cost-effectiveness, and rapid prototyping, to produce custom-made brain matrices based on specific morphometric measurements. The developed protocol is user-friendly and incorporates features such as embossed identifying markers and support structures for challenging thin regions, thereby enhancing its practical utility. Our method demonstrates rapid and cost-effective fabrication of custom brain matrices, significantly reducing both material expenses and production time compared to traditional manufacturing techniques and ready-made products. This work contributes to the growing application of 3D printing in biomedical research, offering a valuable tool for neuroscientists requiring precise and consistent brain tissue sectioning.